New Book: Ideas and Actionable Steps for Scaling Africa’s Blue Economy Strategy - Francis Onditi; Douglas Yates; Narnia Bohler-Muller (The Thinker)
Illusions of Location Theory: Consequences for Blue Economy in Africa, a new book edited by Dr. Francis Onditi and Prof. Douglas Yates, with a foreword by Prof. Narnia Bohler-Muller, is finally published and can now be ordered from global leading platforms, including Amazon.